Hexis of the Body and the Project of Active Piety in Islamic Early Childhood Education in Solo - Tanfidiyah, Nur; Sirait, Sangkot (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study addresses the limited scholarly attention given to the role of the body in shaping religious piety within early childhood education, particularly in Islamic-based institutions. While most studies on piety emphasize cognitive, doctrinal, or socio-political dimensions, little is known about how bodily practices contribute to the internalization of religious values from an early age. Therefore, this research aims to reveal the significant role of the body in the project of piety within Islamic-based Early Childhood Education institutions, specifically Raudlatul Athfal (RA) Ummah 5. In teaching Islam, RA Ummah 5 emphasizes the importance of bodily discipline.Design/methods/approach – This research employed an ethnographic approach. Data collection was conducted through participatory observation to capture children’s activities during both classroom and outdoor learning processes. In addition, in-depth interviews were carried out with the RA principal and teachers, and relevant documents were gathered to strengthen the findings. Through the ethnographic approach, the study explored the specific cultural patterns practiced at RA Ummah 5. Data were analyzed using Miles, Huberman, and Saldaña’s framework, which includes data collection, display, reduction, and verification/conclusion drawing.Findings – The piety project developed at RA Ummah 5 cannot be linked to the market or radicalism; instead, the institution defines its own model of piety based on foundational texts (the Qur’an and Hadith) interpreted textually. This aligns with the ideology rooted in the practices of the Prophet and the third generation of Muslims after him. Bodily practices reflect a discursive Islamic tradition connected to the past and validated by the continuity of practices transmitted across generations. In other words, RA Ummah 5 seeks to construct a future Islam that mirrors the past, distancing itself from modernity by reviving and sustaining traditional Islamic practices.Research implications/limitations – This study is limited in scope as it focuses on a single institution with a small number of respondents. Future research should expand to include more diverse contexts and participants to provide deeper and more comprehensive insights. Researchers should also develop a broader understanding of the research setting to enhance data collection.Practical implications – The findings provide new insights for educators, suggesting that hexis can serve as a means of shaping and controlling children’s behavior to achieve specific educational visions. Originality/value – This study contributes to the literature by demonstrating how RA Ummah 5 constructs its own version of piety—nurturing a rabbani generation that is spiritually, emotionally, and intellectually intelligent. The form of piety developed through bodily hexis is neither dictated by the market nor aligned with radicalism, as often emphasized in prior studies. Instead, this research highlights how bodily hexis is strategically employed as a medium for transmitting and internalizing Islamic values in early childhood education, in accordance with the ideology constructed by the school.Paper type Research paper